A Nationwide Retrospective Analysis of Socioeconomic Factors Associated With Eosinophilic Colitis: A Population-Based Study - Bibek Karki; Samjhana Belbase; Michelle Bernshteyn; Ajit Brar; Hussain Murtaza; Nikky Maharjan; Navindra Dhakal; Subash Ghimire; Pujan Kandel; Calvin Ghimire; Philip McDonald; Matthew Lincoln; et al. (Gastro Hep Advances)
Background and Aims: Eosinophilic colitis (EC) is a rare gastrointestinal inflammation of the colon characterized by eosinophilic infiltration into the colonic wall. The study aimed to assess the socioeconomic factors associated with EC. Methods: A retrospective cohort study was conducted using the 2016–2020 National Inpatient Sample, including adult patients (≥18 years) admitted with EC. Results: Among 4353 EC cases identified, males are more likely to be hospitalized than females (51.8% vs 48.2%, P < .001). Caucasians consisted of 81.7% of total cases, followed by African Americans (8.1%), Hispanics (6.3%), and Asians (1.3%) (P < .001). 50.6% of EC cases had Private/Health Maintenance Organization insurance followed by Medicare (26.5%), Medicaid (15.7%), and 7.2% were uninsured (P < .001). Only 16.5% of patients had a Charlson Comorbidity Index ≥3. Conclusion: Caucasians, males, and those with private insurance were more likely to be diagnosed with EC. The correlation between insurance coverage and hospitalizations shows health-care disparities and implies the need for equitable health-care delivery.